2020
DOI: 10.1007/s11238-020-09794-w
|View full text |Cite
|
Sign up to set email alerts
|

Construal level theory and escalation of commitment

Abstract: Escalation of commitment causes people to continue a failing course of action. We study the role of construal level in such escalation of commitment. Consistent with the widely held view of construal level as a primed effect, we employed a commonly used prime for manipulating this construct in a laboratory experiment. Our findings revealed that the prime failed to produce statistically significant differences in construal level, which was measured using the Behavior Identification Form (BIF). Furthermore, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Schindehutte and Morris, 2016) where students have real-life experiences in concrete contexts (Leitch et al, 2012, as in poverty; are particularly important for promoting psychological closeness and increasing the feasibility of a behavior or event (e.g. Benschop et al, 2020). By taking entrepreneurial action and practicing (Neck et al, 2014) in social and commercially oriented contexts, students decrease the temporal, spatial and hypothetical distance to entrepreneurship, learn to focus on details and thus develop their concrete entrepreneurial mindset.…”
Section: Mental Represen Tations Of Eismentioning
confidence: 99%
“…Schindehutte and Morris, 2016) where students have real-life experiences in concrete contexts (Leitch et al, 2012, as in poverty; are particularly important for promoting psychological closeness and increasing the feasibility of a behavior or event (e.g. Benschop et al, 2020). By taking entrepreneurial action and practicing (Neck et al, 2014) in social and commercially oriented contexts, students decrease the temporal, spatial and hypothetical distance to entrepreneurship, learn to focus on details and thus develop their concrete entrepreneurial mindset.…”
Section: Mental Represen Tations Of Eismentioning
confidence: 99%
“…We can expand our theory based on findings from previous studies, which have demonstrated that people with higher construal levels can think of more benefits for a project and are more likely to continue as a result of negative feedback [86]. In contrast, people move to lower-level identities when the task is difficult, or complex, or when their performance is disrupted [34].…”
Section: A General Discussionmentioning
confidence: 91%
“…The incentivized poker-based task used in the present experiments has several advantages over standard EoC paradigms such as hypothetical investment scenarios (e.g., Staw, 1976;Garland and Newport, 1991;Schulz-Hardt et al, 2009;Feldman and Wong, 2018;Benschop et al, 2020;Lee et al, 2020), or paradigms using Doerflinger et al 10.3389/fpsyg.2022.1025181 Frontiers in Psychology 16 frontiersin.org deception (e.g., Strube and Lott, 1984;Schulz-Hardt et al, 2009). The rules of the task are fully and transparently described to the participants.…”
Section: Variable Investment Poker Taskmentioning
confidence: 99%